PRO-KONTRA PEMULANGAN WARGA NEGARA INDONESIA EKS ISIS - Hakim, Abdurrahman (Al-Daulah : Journal of Criminal Law and State Administration Law, 2020)
This paper aims to analyze the policies of the government that decides do not repatriate former Indonesian citizens of sympathizers ISIS in Iraq and Syria. The theory that used to analyze the case is the theory of maqashid al-shari'ah Jasser Auda. Theories of maqashid al-shari'ah Jasser Auda considered very relevantly in this case because of the ideas that were brought to consider universal human rights enforcement. This is different from the previous theory of maqashid al-shari'ah which only had individual function protection and preservation. Theory of maqashid al-shari'ah Jasser Auda is a reconstruction of the concept of previous scholars with the aim of revitalizing the values of maqoshid value with contemporary problems, especially in terms of enforcement of the human rights (hifdzu al-nafs). In addition, the writer considers that the idea of human rights has a correlation with article 28J paragraphs 1 and 2 of the 1945 Constitution which forms the basis of limitations on the fulfillment of individual rights. Next, not all ISIS sympathizers are the perpetrators of terrorism, therefore the writer offers a de-radicalization effort for children and sympathizers' wives before returning to community life. As victims, they have the right education on the good ideology (hifdzu al-aql) and still carry out the function of heredity (hifdzu al-nasl).